High‐Responsivity Photodetection by a Self‐Catalyzed Phase‐Pure p‐GaAs Nanowire. Issue 17 (3rd April 2018) - Ali, Hassan; Zhang, Yunyan; Tang, Jing; Peng, Kai; Sun, Sibai; Sun, Yue; Song, Feilong; Falak, Attia; Wu, Shiyao; Qian, Chenjiang; Wang, Meng; Zuo, Zhanchun; et al.
Abstract: Defects are detrimental for optoelectronics devices, such as stacking faults can form carrier‐transportation barriers, and foreign impurities (Au) with deep‐energy levels can form carrier traps and nonradiative recombination centers. Here, self‐catalyzed p‐type GaAs nanowires (NWs) with a pure zinc blende (ZB) structure are first developed, and then a photodetector made from these NWs is fabricated. Due to the absence of stacking faults and suppression of large amount of defects with deep energy levels, the photodetector exhibits room‐temperature high photoresponsivity of 1.45 × 10 5 A W −1 and excellent specific detectivity ( D *) up to 1.48 × 10 14 Jones for a low‐intensity light signal of wavelength 632.8 nm, which outperforms previously reported NW‐based photodetectors. These results demonstrate these self‐catalyzed pure‐ZB GaAs NWs to be promising candidates for optoelectronics applications. Abstract : Photodetectors have a large range of applications in environmental monitoring, industrial quality control, and optical communications and nanowire photodetectors with high detectivity and responsivity are desirable. A photodetector is designed and fabricated based on a phase‐pure p‐GaAs single nanowire. It has remarkable photodetection parameters, outperforms previously reported nanowire photodetectors, and can be used for different applications.